2015
DOI: 10.1007/s11356-015-4430-x
|View full text |Cite
|
Sign up to set email alerts
|

Alkylphenol ethoxylates and brominated flame retardants in water, fish (carp) and sediment samples from the Vaal River, South Africa

Abstract: Alkylphenol ethoxylates (APEs) and brominated flame retardants (BFRs) are known to be bio-accumulative, persistent, and endocrine disruptors and can cause adverse health effects in animals and humans. In this study, environmental samples were collected from sites along the Vaal River, South Africa in order to determine the concentrations of APEs and BFRs in water, sediment, and fish samples. The highest concentrations of these pollutants were observed from discharge of the Rietspruit WWTW. Measurable levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…Cleaning products used in domestic and industrial applications (detergents and soaps) can include non-ionic surfactants such as alkylphenol ethoxylates (AEOs), of which more than 90% are nonylphenol ethoxylates (NPEOs) (Farré et al, 2008). Compounds of interest include 4'nonylphenol, a well-known metabolite of NPEOs which has recently been detected up to 80 ng/L in the Vaal River, South Africa (Chokwe et al, 2015).…”
Section: Personal Care Products (Pcps)mentioning
confidence: 99%
“…Cleaning products used in domestic and industrial applications (detergents and soaps) can include non-ionic surfactants such as alkylphenol ethoxylates (AEOs), of which more than 90% are nonylphenol ethoxylates (NPEOs) (Farré et al, 2008). Compounds of interest include 4'nonylphenol, a well-known metabolite of NPEOs which has recently been detected up to 80 ng/L in the Vaal River, South Africa (Chokwe et al, 2015).…”
Section: Personal Care Products (Pcps)mentioning
confidence: 99%
“…Brominated flame retardants (BFRs) are classified as industrial chemicals with high production volume and are mainly employed for fire retardation purposes (WHO/IPCS 1994, 1997. Among these groups of chemicals, polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane (HBCDD) and tetrabromobisphenol A (TBBPA) have been critically evaluated due to their ubiquitous distribution in the environment (Chokwe et al 2015, Muenhor et al 2010, Zeng et al 2014. As a result of their excellent flame retardant properties, some of these chemicals are still widely used in different industrial applications (Gorga et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Polybrominated diphenyl ethers (PBDEs) are a class of BFRs and man-made non-naturally occurring chemicals utilized extensively as additives in a wide variety of consumer products, such as electronic devices, vehicles, building materials, airplanes, ships, and furniture foam and upholstery. Owing to their environmental persistence and accumulation in adipose tissues, PBDEs are ubiquitous in the atmospheric environment (Chao et al, 2014a;Cincinelli et al, 2014;Zhou et al, 2014;Shy et al, 2015), in soils, sediments, and plants , water and fishes (Chokwe et al, 2015), and marine and terrestrial mammals (Leonel et al, 2014;Vetter et al, 2015). The animal studies showed that PBDEs disrupted thyroid function and spermatogenesis (Bowers et al, 2015;Huang et al, 2015), impaired mitochondrial function (Huang et al, 2015), induced hepatotoxicity (Ćurčić et al, 2015), caused developmental abnormalities (Berger et al, 2014), affects neurological behaviour (Costa and Giordano, 2011).…”
Section: Introductionmentioning
confidence: 99%